Economic approach of law - Miceli, Thomas J. (Stanford Stanford University Press, 2017)
The third edition of this seminal textbook is thoroughly updated to include recent cases and the latest scholarship, with particular attention paid to torts, contracts, property rights, and the economics of crime. A new chapter organization, ideal for quarter- or semester-long courses, strengthens the book's focus on unifying themes in the field. As Miceli tells a cohesive, analytical "story" about law from a distinctly economic perspective, exercises and problems encourage students to deepen their knowledge.